Ruggedized sensor packaging with advanced die attach and encapsulation material for harsh environment - Tay, Yu Shan (2024)
Current gas sensors are typically graded for performance up to 100 °C and limited by the materials used in their packaging. This work aims to select, design and investigate novel materials for die attach and encapsulation technology, such as copper nanoparticles-based die attach and phthalonitrile-based encapsulant, for the fabrication of a packaged gas sensor for harsh environment applications. This is done through a series of test protocols and reliability assessments developed to simulate operations at high temperature and under strong vibration.